Training teachers for English Medium Instruction: lessons from research on second language listening comprehension - María Ángeles Martín del Pozo (Revista de Lingüística y Lenguas Aplicadas)
CLIL (Content and Language Integrated Learning) and EMI (English Medium Instruction) practices have outpaced theory and teacher training. There is a need to provide answers to some of the key issues such as the language requirements. This paper aims to show that knowledge from English for Specific Purposes and English for Academic Purposes, fields which have provided effective teaching practices and materials, could now be used in CLIL/EMI. The paper focuses on two of these. First, the issues related to second language academic listening comprehension and, secondly, the findings from research on it and their implications for student / lecturer training and materials design. These implications and suggestions are summarized. The paper concludes providing some language learning resources originally targeted to students but which could become tools for (self) training of those teachers who need to update their language skills for CLIL.